Examen especial de la cuenta caja - bancos de la corporación de productores agroecológicos frutas tropicales "San Miguel de Brasil" de la parroquia el Cambio cantón Machala, provincia de el Oro, periodo del 01 de enero al 31 de diciembre del 2015 - Jaramillo Calle, Teonila Del Carmen (2017)
The Special Review made to the Caja - Bancos account of the Agroecological Producers Corporation "San Miguel de Brasil" of the El Cantón Machala parish, Province of El Oro, from January 1 to December 31, 2015 Executed to meet a requirement, prior to choosing the Degree in Accounting and Auditing, Public Accountant - Auditor at the National University of Loja, in addition to the requirement to establish the reasonableness of the balance of the bank account presented In the Financial Statements as well as to evaluate the Internal Control System implemented by the entity, applying Legal provisions, Auditing Principles and Norms. Prior to the execution of the thesis, objectives were set out which were fulfilled in their totality, techniques and procedures of the investigation were applied as audit techniques oriented to the Special Examination in its three phases Planning, Execution, Final Report, complementing with the followup And monitoring; In this way, the Internal Control System was evaluated by means of the application of questionnaires in order to examine the risk, on the basis of this, to provide evidence of compliance and substantive tests that led to the determination of the reasonableness of the Financial Statements; The results of which are reported in the final report through comments, conclusions and recommendations. Once the investigative work is completed, it is concluded that the company does not carry out cash balances and bank reconciliations surprisingly, which does not guarantee the effectiveness of the balances contained in the Financial Statements, which is why it is recommended to correct these practices in order to detect errors Or omissions for better profitability and thus improve administrative and financial management.